1944
DOI: 10.1104/pp.19.2.310
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moisture and of Treatments With Acid and Alkali on Rate of Formation of Free Fatty Acids in Stored Cottonseed

Abstract: IntroductionCottoniseed deteriorates upon1 storage, with the result that the contenit of free fattv acids in the seed oil is increased, the color of the oil in the seed is darkened, the seed protein is partially denatured, and viability is decreased. This increase in free fatty acid conitent is reflected in a higher refining loss during the processing of the crude oil and the darkened color of the oil reduces its desirability as ani edible product. AIALOWAN (7,8), FREYER (3), anid ROBERTSON anid CAMPBELL (14) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1946
1946
1958
1958

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…7. When seedlings were allowed to develop in the dark in temperatures ranging from 210 to 390 C, there was no alteration in the pattern of fat utilization found at 300 C. 8. Under all germination conditions tested, the fat composition was the same function of the total amount of fatty acids remaining in the fat reserve; it was independent of the rate or type of seedling development.…”
Section: Experiments and Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…7. When seedlings were allowed to develop in the dark in temperatures ranging from 210 to 390 C, there was no alteration in the pattern of fat utilization found at 300 C. 8. Under all germination conditions tested, the fat composition was the same function of the total amount of fatty acids remaining in the fat reserve; it was independent of the rate or type of seedling development.…”
Section: Experiments and Resultsmentioning
confidence: 89%
“…Evidence, however, for an initially low lipase activity appears in the literature. Karon and Altschul (8) suggested that the autocatalytic reaction which they found typical of free fatty acid formation in moist cotton seeds might be dependent on an increase in lipase aetivitv with time. Olcott and Fontaine (14) could not detect lipase in dormant cotton seeds, but in another study they (15) showed that during germination the activity of this enzyme increased to a maximum.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Two of the preselnt authors have reported previously (13) that ammonia and hydrochloric acid vapors inhibit lipolysis of the oil in cottonseed. Subsequent experiments indicated that ammonia treatment also effects the speetruin of extracted cottonseed oil and the heating of seed stored in bulk (1).…”
Section: Introductionmentioning
confidence: 99%
“…It is not possible, then, on the basis of moisture content alone, to predict respiration intensity. Similarly, it has been previously shown (8) that it is impossible to predict the rate of free fatty acid production in cottonseed on the basis of moisture content alone. 4.…”
mentioning
confidence: 99%
“…Whenever it was necessary to change the moisture content artificially either above or below its original value, care was taken to so condition the seeds to the desired moisture content that any resulting biochemical activity would be minimized and permanent injury to the seeds would be prevented. Conditioning was accomplished in this manner by carrying out all moisture changes in a cold room, as previously described (8). Each 3-pound lot of seeds was then stored in air-tight jars at 250 C.…”
mentioning
confidence: 99%